Use of Indicator Methods for the Purposes of Monitoring Sustainable Energy in the Region - Małgorzata Trojanowska; Krzysztof Nęcka (Barometr Regionalny)
Implementation of the conception of sustainable energy requires a progress evaluation, which calls for an indicator system for monitoring sustainable energy. In this paper it is proposed to use simultaneously two systems, one based on a set of specific indicators and the other on a synthetic indicator. The usefulness of proposed indicator methods was checked on the example of rural areas of the Śląskie Voivodship by monitoring sustainable energy in given counties in 2004 and 2014.